Trend Analysis of Groundwater Level, Rainfall and Area under Groundwater Irrigation in Ropar District of Punjab - Tanish Kumar; Mahesh Chand Singh; JP Singh (Journal of Soil Salinity and Water Quality, 2023)
The present investigation was undertaken to study and detect trend in long-term recorded groundwater level, rainfall and area under tube wells using non-parametric methods (Mann-Kendall’s trend test, Sen’s slope test, Pettitt’s test and Standard Normal Homogeneity Test) in XLSTAT software. All four tests confirmed an increasing trend and change-point existence in groundwater level in Ropar district both during pre-and post-monsoon periods. Similarly, trend was recorded in long-term rainfall in the different parts (blocks) of the district, particularly during post-monsoon period. Moreover, an increasing trend in area under tube wells was confirmed by all the four tests. The increasing depth of groundwater levels in different villages/blocks in relation to increasing number of tube wells (over-exploitation of groundwater resources) and non-uniform rainfall distribution is becoming a serious threat in terms of water availability in future. Thus, monitoring and analysing groundwater level, rainfall and area under tube wells in the district as well as on state level using non-parametric tests may be useful to manage the available groundwater resources, plan crops and predict the futuristic scenario of the water resources.